Development and Validation of a Stability-Indicating RP-HPLC Method for the Quantitative Analysis of Anagrelide Hydrochloride - Pujeri, Sudhakar S. (Österreichische Apotheker-Verlagsgesellschaft, 2012)
A simple, rapid, and stability-indicating reverse-phase liquid chromatographic assay method was developed for Anagrelide Hydrochloride (ANG) in the presence of its degradation products generated from forced decomposition studies. The HPLC separation was achieved on a C18 Inertsil column (250 mm × 4.6 mm i.d. particle size is 5 μm), using solution A, a mixture of 0.03 M potassium di-hydrogen phosphate pH-adjusted to 3.0 using ortho-phosphoric acid (buffer): methanol: acetonitrile (90:5:5, v/v/v), and solution B, which contains a mixture of buffer: acetonitrile (10:90, v/v). The UV detector was operated at 251 nm while column temperature was maintained at 40°C, and the gradient program had the flow rate of 1.0 mL min(−1). The developed method was validated as per ICH guidelines with respect to specificity, linearity, precision, accuracy, robustness, and limit of quantification. The method was found to be simple, specific, precise, accurate, and reproducible. Selectivity was validated by subjecting the stock solution of ANG to acidic, basic, photolysis, oxidative, and thermal degradation. The calibration curve was found to be linear in the concentration range of 0.05–152 μg mL(−1) (R(2) = 0.9991). The peaks of degradation products did not interfere with that of pure ANG. The utility of the developed method was examined by analyzing the tablets containing ANG.